2012
DOI: 10.5336/medsci.2011-25368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pre-Emptive Pregabalin with Placebo and Diclofenac Combination for Postoperative Analgesia and Cognitive Functions After Laparoscopic Cholecystectomy

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : This study was conducted to evaluate the efficacy of pre-emptive pregabalin compared with plasebo and diclofenac combination for attenuating postoperative pain, analgesic consumption and cognitive function after laparoscopic cholecystectomy. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Sixty adults with ASA physical status I-III of either sex undergoing elective laparoscopic cholecystectomy were included in this prospective, randomized plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…A pilot study by Leung et al. found that postoperative use of gabapentin decreased the incidence of delirium, and concluded that this was probably secondary to an opioid sparing effect .…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study by Leung et al. found that postoperative use of gabapentin decreased the incidence of delirium, and concluded that this was probably secondary to an opioid sparing effect .…”
Section: Discussionmentioning
confidence: 99%
“…27 Akarsu et al reported delayed recovery times with pregabalin, as a result of their study comparing 300 mg pregabalin with placebo-diclofenac combination in 60 patients. 28 In their study where the effects of different doses of pregabalin premedication on hemodynamic responses were evaluated, Rastogi et al found that there was no difference between groups in terms of recovery. 26 In our study, the distribution of the groups was similar in terms of operation time, recovery time and first analgesic initiation time.…”
Section: Discussionmentioning
confidence: 99%
“…Yine Akarsu ve ark. [14] laparoskopik kolesistektomiden bir saat önce verilen 300 mg pregabalinin, ağrı ve analjezik tüketimini azalttığını bildirmişlerdir. Cabrera Schulmeyer ve ark.…”
Section: Discussionunclassified
“…Antinosiseptif etkisi, bu kanallar aracılığı ile kalsiyum girişinin ve takibinde primer afferent sinir liflerinden uyarıcı nörotransmitterlerin salınımının inhibisyonu ile oluşabilir. [13,14] Bu süreç, periferde ağrı olarak algılanan santral duyarlılığı azaltır. Bu alt ünitelere bağlanma afinitesi ve etki gücü gabapentinden altı kez daha fazladır.…”
Section: Discussionunclassified
See 1 more Smart Citation